2014
DOI: 10.1177/0009922814547564
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Management of Home Oxygen for Bronchiolitis

Abstract: Management of home O2 in patients with bronchiolitis is a common in UT and CO. Weaning practices vary. Further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
(25 reference statements)
1
7
1
Order By: Relevance
“…Despite this, the median time to follow‐up among the study population was 3 days. In contrast to our findings, in a survey of Colorado and Utah PCPs who have managed patients with bronchiolitis on home oxygen, 85% of PCPs reported that they generally see patients within 1–2 days of ED discharge . Similarly, Flett et al found that outpatient follow‐up occurred > 24 hours later in only 17.5% of patients discharged home on oxygen.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite this, the median time to follow‐up among the study population was 3 days. In contrast to our findings, in a survey of Colorado and Utah PCPs who have managed patients with bronchiolitis on home oxygen, 85% of PCPs reported that they generally see patients within 1–2 days of ED discharge . Similarly, Flett et al found that outpatient follow‐up occurred > 24 hours later in only 17.5% of patients discharged home on oxygen.…”
Section: Discussioncontrasting
confidence: 99%
“…It is unclear whether delay in follow‐up among our subjects was due to caregiver failure to schedule an appointment, low appointment availability due to high clinic volumes, or recommendation of PCPs. Previous studies have shown that there are a variety of oxygen weaning methods employed by PCPs, including telephone follow‐up and incremental weaning of oxygen at home, which may be dictating the timing of follow‐up visits . It is reassuring, however, that delay in follow‐up was not associated with return ED visits or adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in our region of Michigan (encompassing 3 counties) only 8% of pediatricians and family medicine providers had prior experience with home oxygen therapy for bronchiolitis, lower than the reported 15% in a national sample of American Academy of Pediatrics members. 8 Despite the fact that, at altitude, home oxygen therapy for bronchiolitis has continued to be a safe and effective practice 9 with 90% of providers in these areas reporting experience, 7 our results are consistent with the findings that very few physicians at sea level have reported experience or comfort with this practice. 8 It was surprising that even with a total lack of literature regarding family medicine providers’ use of home oxygen therapy for bronchiolitis, our family medicine providers reported experience with this practice twice as frequently as compared with our pediatricians (12.1% vs 6.2%, P = .3).…”
Section: Discussionsupporting
confidence: 81%
“…Questions were developed by the research team after a literature review 7-9 and were pilot tested. Surveys were pilot tested with 3 independent groups and questions/response options were refined based on feedback.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation